Spectra and structural polynomials of graphs of relevance to the theory of molecular conduction - Fowler, Patrick W. (Ars mathematica contemporanea, 2017)
In chemistry and physics, distortivity of ?$π$?-systems (stabilisation of bond-alternated structures) is an important factor in the calculation of geometric, energetic, and electronic properties of molecules via graph theoretical methods. We use the spectra of paths and cycles with alternating vertex and edge weights to obtain the eigenvalues and eigenvectors for a class of linear and cyclic ladders with alternating rung and backbone edge weights. We derive characteristic polynomials and other structural polynomials formed from the cofactors of the characteristic matrix for these graphs. We also obtain spectra and structural polynomials for ladders with flipped weights and/or Möbius topology. In all cases, the structural polynomials for the composite graphs are expressed in terms of products of polynomials for graphs of half order. This form of the expressions allows global deductions about the transmission spectra of molecular devices in the graph-theoretical theory of ballistic molecular conduction.
Keywords: karakteristični polinom; lastne vrednosti; matrika sosednosti; molekulska prevodnost; uteženi grafi